LIVEABILITY IN A GARDEN CITY – A CASE STUDY OF PODKOWA LEŚNA (POLAND) - Barucka, Edīta (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The first garden cities in the early 20th century were designed to provide a wholesome alternative to increasingly congested cities. They were characterised by low-density building amongst generous verdure, the presence of open public spaces, and of cultural and educational institutions. Interestingly, the goals and priorities of the Garden City Movement presaged much of the agenda of contemporary sustainable planning. This article sets out to highlight the ecological and social potential of the garden city model and to assess its relevance for current debates on liveability through a case study of Podkowa Leśna in Poland. The argument draws considerably on the analysis of reports issued by the municipal council of Podkowa Leśna and the Town and Country Planning Association in Britain. One of the main issues addressed concerns the heritage of green and open spaces and the legacy of community values in historical garden cities.